2014
DOI: 10.1016/j.jhep.2013.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Increased brain lactate is central to the development of brain edema in rats with chronic liver disease

Abstract: The pathogenesis of brain edema in patients with chronic liver disease (CLD) and minimal hepatic encephalopathy (HE) remains undefined. This study evaluated the role of brain lactate, glutamine and organic osmolytes, including myo-inositol and taurine, in the development of brain edema in a rat model of cirrhosis.Six-week bile-duct ligated (BDL) rats were injected with (13)C-glucose and de novo synthesis of lactate, and glutamine in the brain was quantified using (13)C nuclear magnetic resonance spectroscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 58 publications
4
51
5
Order By: Relevance
“…Gln increased linearly reaching a 2.5 fold increase at week 8. We measured a gradual decrease of Ins together with other osmolytes as tCho and Cr, in agreement with previously published studies in BDL rats (Chavarria et al 2013;Bosoi et al 2014) and CLD patients (Kreis et al 1992;Bluml et al 1998;Taylor-Robinson et al 1999), suggesting a compensatory effect for the osmotic imbalance created by Gln accumulation,. Therefore, as expected, Gln most strongly correlated with Ins, consistent with the fact that Ins is considered as the main astrocytic osmolyte (Lien et al 1990;Flögel et al 1995).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Gln increased linearly reaching a 2.5 fold increase at week 8. We measured a gradual decrease of Ins together with other osmolytes as tCho and Cr, in agreement with previously published studies in BDL rats (Chavarria et al 2013;Bosoi et al 2014) and CLD patients (Kreis et al 1992;Bluml et al 1998;Taylor-Robinson et al 1999), suggesting a compensatory effect for the osmotic imbalance created by Gln accumulation,. Therefore, as expected, Gln most strongly correlated with Ins, consistent with the fact that Ins is considered as the main astrocytic osmolyte (Lien et al 1990;Flögel et al 1995).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the sum of the main osmolytes (Gln, Ins, tCho, Cr) was not constant over time, showing a 20 % increase at week 8. This progressive yet incomplete osmotic compensation is probably the underlying cause of the observed minimal brain edema associated with chronic HE, as previously shown Bosoi et al 2014). Moreover these changes go along with the appearance of the neurological signs towards the end stage of the disease, as demonstrated by the decrease in locomotor activity in the Open Field task using the same animal model (Leke et al 2012;Rackayova et al 2015).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…This phenomenon might be attributed to hyperplasia of bile duct epithelial cells after BDL, which is a key factor and center pathological link to a series of lipid peroxidation reactions [19] . Recent animal study found that de novo synthesis of lactate in rat brain is one of the main reasons for the occurrence of cerebral edema six weeks after BDL [34] . Decreased levels of glutamine synthetase and glutaminase in the liver also contributed to cause hyperammonemia [35] .…”
Section: Carbon Tetrachloride (Ccl 4 )mentioning
confidence: 99%